MANAGEMENT OF FOREIGN ECONOMIC PERFORMANCE OF EXPORTORIENTED ENTERPRISE IN THE SYSTEM OF “SMART-CUSTOMS” - SAVITSKYI, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article researches the issue of managing the foreign economic performance of export-oriented enterprise in the system of "Smart Customs" under current conditions of integration. The significance and impact of Ukraine`s integration processes to the European Union on the customs procedures reformation and process of supplying goods to foreign markets has been argued. The dynamics of completed customs declarations during 2014-2023 has been analyzed: the indicators that concerns paper customs declarations of export and import of goods; the indicators that deals with digital way of decorations of transporting goods through the customs checkpoints. As a result, the key trends in the digitalization development of customs documents arrangements emphasized. The advantages and problems of digitizing customs practice in Ukraine have been established and substantiated with the consideration of adaptive periods of performance and supply under current war state. Therefore, the link between necessary customs law changes and real demands of European Union legislation in the sphere of customs digitalization has been underlined. The application of basic and specialized tools of "E-Customs" and "Smart Customs" system in activating foreign economic performance of national enterprises that are opened for usage by Ukrainian producers, suppliers and agents has been characterized. The main elements of foreign economic activity management of export-oriented enterprise that concerns documents flow during customs clearance, compliance with the customs legislation of Ukraine, conducting automated analysis of risk identification, detailed planning of transporting stages, information about the status of goods movement while transiting between customs checkpoints have been defined. An organizational scheme of foreign economic activity management process of export-oriented enterprise based on the digitalization of customs procedures under integration conditions has been proposed and built. Through the relations between responsible specialists of export-oriented enterprise performance, there was emphasized the stage of preparation that includes adaptation to the current demands of integration and the stage of realization.
Keywords: foreign economic activity management; export-oriented enterprise; integration; customs clearance; digitalization of customs procedures; Smart Customs" system tools